Legal Analysis On The Protection Of Employees On Actions Of Termination Of Employment Relations Due To Serious Violations - Oky Oktarina Mooduto (Estudiante Law Journal, 2019)
This study aims to determine the legal protection of employees who receive termination of employment without any legal process at PT. Karsa Utama Gorontalo City and to find out what the factors causing some employees at PT. Karsa Utama Gorontalo City was terminated without any legal process. The type of research in this thesis uses empirical legal research, which is supported by field data. Meanwhile, judging from its nature, it includes qualitative descriptive research. The data used are primary in the form of interviews and secondary data in the form of library research. The results of the study show legal protection for employees who receive termination of employment without any legal process at PT. Karsa Utama Gorontalo City has been regulated and confirmed in the Constitutional Court Decision No. 012/PUU-I/2003, which revoked the provisions of Article 158 of Law no. 13 of 2003 concerning Manpower, which is also confirmed by the issuance of the Circular Letter of the Minister of Manpower and Transmigration numbered SE-13/MEN/SJ-HK/I/2005 dated January 7, 2005. Where in point 3 letter a of the Ministerial Circular Letter it is stated that the layoffs are because workers commit Serious mistakes including theft (ex Article 158 paragraph (1) of Law No. 13 of 2003) can only be committed after a criminal decision has permanent legal force. The factors that cause so that some employees at PT. Karsa Utama Gorontalo City got termination of employment without any legal process, namely because it was based on the reason for a serious error committed by 10 employees of PT. Karsa Utama Gorontalo. It is also based on company regulations and work agreements that have been mutually agreed upon by all employees of PT. Karsa Utama. This step is an effort by the company to wipe out employee fraud and make employees at PT. Karsa Utama has a good attitude or behavior while working..Keywords: Legal Protection, Employees, Termination of Employment.